A Randomized Controlled Trial Evaluating a Low-Volume PEG Solution Plus Ascorbic Acid versus Standard PEG Solution in Bowel Preparation for Colonoscopy. (15th November 2015) - Tajika, Masahiro; Tanaka, Tsutomu; Ishihara, Makoto; Mizuno, Nobumasa; Hara, Kazuo; Hijioka, Susumu; Imaoka, Hiroshi; Sato, Takamitsu; Yogi, Tatsuji; Tsutsumi, Hideharu; Fujiyoshi, Toshihisa; Hieda, Nobuhiro; et al.
Abstract : Evaluation of polyethylene glycol electrolyte lavage solution containing ascorbic acid (PEG-ASC) has been controversial in the point of its hyperosmolarity, especially in old population. So we therefore designed the present study to compare the efficacy, acceptability, tolerability, and safety of 1.5 L PEG+ASC and 2 L standard PEG electrolyte solution (PEG-ELS), not only in the general population, but also in patients of advanced age. Randomization was stratified by age (<70 years or 70> years), and hematological and biochemical parameters were compared in each age group, especially with respect to the safety profile of each regimen. As a result, the 1.5-L PEG-ASC regimen had higher patient acceptability than the 2-L PEG-ELS regimen. Tolerability, bowel cleansing, and safety were similar between regimens. However, we demonstrated significant statistical changes in the hematological and biochemical parameters after taking bowel preparation solutions, not only in the PEG+ASC group, but also in the PEG-ELS group. No significant differences in the safety profile were found between subjects aged less than 70 years and those aged 70 years or more; nevertheless, regardless of age, proper hydration is needed throughout the bowel preparation process.